Whole Genome Sequencing Prioritizes CHEK2, EWSR1, and TIAM1 as Possible Predisposition Genes for Familial Non-Medullary Thyroid Cancer - Srivastava, Aayushi; Giangiobbe, Sara; Skopelitou, Diamanto; Miao, Beiping; Paramasivam, Nagarajan; Diquigiovanni, Chiara; Bonora, Elena; Hemminki, Kari; Försti, Asta; Bandapalli, Obul Reddy (Frontiers in Endocrinology, 2021)
Familial inheritance in non-medullary thyroid cancer (NMTC) is an area that has yet to be adequately explored. Despite evidence suggesting strong familial clustering of non-syndromic NMTC, known variants still account for a very small percentage of the genetic burden. In a recent whole genome sequencing (WGS) study of five families with several NMTCs, we shortlisted promising variants with the help of our in-house developed Familial Cancer Variant Prioritization Pipeline (FCVPPv2). Here, we report potentially disease-causing variants in checkpoint kinase 2 (CHEK2), Ewing sarcoma breakpoint region 1 (EWSR1) and T-lymphoma invasion and metastasis-inducing protein 1 (TIAM1) in one family. Performing WGS on three cases, one probable case and one healthy individual in a family with familial NMTC left us with 112254 variants with a minor allele frequency of less than 0.1%, which was reduced by pedigree-based filtering to 6368. Application of the pipeline led to the prioritization of 7 coding and 9 non-coding variants from this family. The variant identified in CHEK2, a known tumor suppressor gene involved in DNA damage-induced DNA repair, cell cycle arrest, and apoptosis, has been previously identified as a germline variant in breast and prostate cancer and has been functionally validated by Roeb et al. in a yeast-based assay to have an intermediate effect on protein function. We thus hypothesized that this family may harbor additional disease-causing variants in other functionally related genes. We evaluated two further variants in EWSR1 and TIAM1 with promising in silico results and reported interaction in the DNA-damage repair pathway. Hence, we propose a polygenic mode of inheritance in this family. As familial NMTC is considered to be more aggressive than its sporadic counterpart, it is important to identify such susceptibility genes and their associated pathways. In this way, the advancement of personalized medicine in NMTC patients can be fostered. We also wish to reopen the discussion on monogenic vs polygenic inheritance in NMTC and instigate further development in this area of research.